Mauritius: Agricultural R&D Indicators Factsheet - Beintema, Nienke; Flaherty, Kathleen; Koyelas, Chandasa; Ramkissoon, Jairaj; Chandrabose, Sembhoo; Perez, Sandra; Ramnauth, Raj (International Food Policy Research Institute, 2019)
This country factsheet presents key agricultural R&D indicators in a highly accessible visual display. The publication also features a more in-depth analysis of some of the key challenges that the country’s agricultural R&D system is facing, and the policy options to address these challenges.